Exploring teachers' understanding and implementation of STEAM: one size does not fit all - Boice, Katherine L.; Alemdar, Meltem; Jackson, Justina R.; Kessler, Talia C.; Choi, Jasmine; Grossman, Sabrina; Usselman, Marion (Frontiers in Education, 2024)
In recent years, STEAM (science, technology, engineering, arts, and math) education has become an increasingly popular tool to promote student learning and engagement across disciplines. However, researchers and practitioners continue to note the lack of clarity around definitions of STEAM, its intended purpose, and the nature of discipline integration. In this paper, we explore teachers' understandings and implementation of STEAM as they participated in a teacher professional learning program. Methods: Using a mixed-methods approach, we analyzed data from four years of program implementation with K-12 teachers across multiple schools and districts (n = 61). Results: Participants' understanding of STEAM was deepened through their involvement in the professional learning program, with many reflecting on their initial, often shallow, (mis)conceptualizations of STEAM. Using an integration continuum developed by the authors, we identified ways in which integration varied across the STEAM lessons teachers developed, contextualizing these findings within the changing educational landscape of the COVID-19 pandemic, as teachers transitioned between remote, hybrid, and in-person instruction. Participants shared their reflections on the personal, professional, and contextual factors that supported and hindered successful STEAM integration. Discussion: We found that, when provided with sustained, collaborative pedagogical and material support, teachers could successfully improve their understanding of STEAM and implement STEAM lessons tailored to their grade-level and disciplinary context. Our findings reinforce that teachers need support, autonomy, and flexibility to adopt an approach to STEAM integration that best fits their classroom and school context. We discuss the implications of these findings for researchers and practitioners working to provide effective STEAM teacher professional learning.